Screening of six medicinal plant species for antileishmanial activity - Ferreira Fabiana Borges Padilha; Cabral Márcia Regina Pereira; Sarragiotto Maria Helena; Fernandez Carla Maria Mariano; Gazim Zilda Cristiani; Junior Ranulfo Piau; Demarchi Izabel Galhardo; Silveira Thaís Gomes Verzignassi; Lonardoni Maria Valdrinez Campana (Acta Pharmaceutica)
This study is aimed to investigate the in vitro anti-leishmanial activity of ethanolic, aqueous or dichloromethane extracts of leaves, flowers, fruits or roots, of six medicinal plant species, namely, Nectandra megapotamica, Brunfelsia uniflora, Myrcianthes pungens, Anona muricata, Hymenaea stigonocarpa and Piper corcovandesis. After isolation and analysis of chemical components by ultra-high performance liquid chromatography-high-resolution tandem mass spectrometry (UHPLC-HRMS/MS), the extracts were also tested for toxicity in J774.A1 macrophages and human erythrocytes. Phenolic acids, flavonoids, acetogenins, alkaloids and lignans were identified in these extracts. Grow inhibition of promastigotes forms of Leishmania amazonensis and Leishmania braziliensis and the cytotoxicity in J774.A1 macrophages were estimated by the XTT method. The most promising results for L. amazonensis and L. braziliensis were shown by the ethanolic extract of the fruits of Hymenaea stigonocarpa and dichloromethane extract of the roots of Piper corcovadensis, with IC50 of 160 and 150 μg mL−1, resp. Ethanolic extracts of A. muricata (leaf), B. uniflora (flower and leaf), M. pungens (fruit and leaf), N. megapotamica (leaf), and aqueous extract of H. stigonocarpa (fruit) showed IC50 > 170 μg mL−1 for L. amazonensis and > 200 μg mL−1 for L. braziliensis. The extracts exhibited low cytotoxicity towards J774.A1 macrophages with CC50 > 1000 μg mL−1 and hemolytic activity from 0 to 46.1 %.